Prediction of clamp-derived insulin sensitivity from the oral glucose insulin sensitivity index - Tura, Andrea; Chemello, Gaetano; Szendroedi, Julia; Göbl, Christian; Færch, Kristine; Vrbíková, Jana; Pacini, Giovanni; Ferrannini, Ele; Roden, Michael (Diabetologia, 2018)
AIMS/HYPOTHESIS: The euglycaemic-hyperinsulinaemic clamp is the gold-standard method for measuring insulin sensitivity, but is less suitable for large clinical trials. Thus, several indices have been developed for evaluating insulin sensitivity from the oral glucose tolerance test (OGTT). However, most of them yield values different from those obtained by the clamp method. The aim of this study was to develop a new index to predict clamp-derived insulin sensitivity (M value) from the OGTT-derived oral glucose insulin sensitivity index (OGIS). METHODS: We analysed datasets of people that underwent both a clamp and an OGTT or meal test, thereby allowing calculation of both the M value and OGIS. The population was divided into a training and a validation cohort (n = 359 and n = 154, respectively). After a stepwise selection approach, the best model for M value prediction was applied to the validation cohort. This cohort was also divided into subgroups according to glucose tolerance, obesity category and age. RESULTS: The new index, called PREDIcted M (PREDIM), was based on OGIS, BMI, 2 h glucose during OGTT and fasting insulin. Bland-Altman analysis revealed a good relationship between the M value and PREDIM in the validation dataset (only 9 of 154 observations outside limits of agreement). Also, no significant differences were found between the M value and PREDIM (equivalence test: p < 0.0063). Subgroup stratification showed that measured M value and PREDIM have a similar ability to detect intergroup differences (p < 0.02, both M value and PREDIM). CONCLUSIONS/INTERPRETATION: The new index PREDIM provides excellent prediction of M values from OGTT or meal data, thereby allowing comparison of insulin sensitivity between studies using different tests.
Keywords: Glucose clamp; stupeň závažnosti nemoci; glukózový toleranční test; Obesity; krevní glukóza; Glucose Clamp Technique; diabetes mellitus; Glucose Intolerance; Time Factors; Validation; inzulin; Middle Aged; Diabetes Mellitus; mužské pohlaví; Insulin; Adult; Prediction model; Glucose tolerance; Oral glucose tolerance test; Blood Glucose; ženské pohlaví; Anthropometry; Humans; Insulin resistance; časové faktory; lidé středního věku; antropometrie; obezita; glykemický clamp; dospělí; porucha glukózové tolerance; inzulinová rezistence; Female; Glucose Tolerance Test; Insulin Resistance; Severity of Illness Index; lidé; Male